Restriction of HIV-1 by Rhesus TRIM5α Is Governed by Alpha Helices in the Linker2 Region - Sastri, Jaya (American Society for Microbiology, 2014)
TRIM5α proteins are a potent barrier to the cross-species transmission of retroviruses. TRIM5α proteins exhibit an ability to self-associate at many levels, ultimately leading to the formation of protein assemblies with hexagonal symmetry in vitro and cytoplasmic assemblies when expressed in cells. However, the role of these assemblies in restriction, the determinants that mediate their formation, and the organization of TRIM5α molecules within these assemblies have remained unclear. Here we show that α-helical elements within the Linker2 region of rhesus macaque TRIM5α govern the ability to form cytoplasmic assemblies in cells and restrict HIV-1 infection. Mutations that reduce α-helix formation by the Linker2 region disrupt assembly and restriction. More importantly, mutations that enhance the α-helical content of the Linker2 region, relative to the wild-type protein, also exhibit an increased ability to form cytoplasmic assemblies and restrict HIV-1 infection. Molecular modeling of the TRIM5α dimer suggests a model in which α-helical elements within the Linker2 region dock to α-helices of the coiled-coil domain, likely establishing proper orientation and spacing of protein domains necessary for assembly and restriction. Collectively, these studies provide critical insight into the determinants governing TRIM5α assembly and restriction and demonstrate that the antiviral potency of TRIM5α proteins can be significantly increased without altering the affinity of SPRY/capsid binding. IMPORTANCE Many members of the tripartite motif (TRIM) family of proteins act as restriction factors that directly inhibit viral infection and activate innate immune signaling pathways. Another common feature of TRIM proteins is the ability to form protein assemblies in the nucleus or the cytoplasm. However, the determinants in TRIM proteins required for assembly and the degree to which assembly affects TRIM protein function have been poorly understood. Here we show that alpha helices in the Linker2 (L2) region of rhesus TRIM5α govern assembly and restriction of HIV-1 infection. Helix-disrupting mutations disrupt the assembly and restriction of HIV-1, while helix-stabilizing mutations enhance assembly and restriction relative to the wild-type protein. Circular dichroism analysis suggests that that the formation of this helical structure is supported by intermolecular interactions with the coiled-coil (CC) domain in the CCL2 dimer. These studies reveal a novel mechanism by which the antiviral activity of TRIM5α proteins can be regulated and provide detailed insight into the assembly determinants of TRIM family proteins.